2021
DOI: 10.1039/d1se00402f
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and electrochemical water oxidation mediated by bis(pyrazol-1-ylmethyl)pyridine-ligated Cu(i) complexes

Abstract: The first CuI-complexes as homogeneous chemically and electrocatalytically driven WOCs operating at low and near-neutral pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 64 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…To investigate the relationship between the structure and catalytic activity and to achieve satisfactory performance of Cu complexes, numerous studies have been devoted to designing ligands with different backbone structures as well as ligands with electron-donating or electron-withdrawing functional groups. 21–26 It has been confirmed that the backbone structure of a ligand has an obvious effect on the catalytic activity of Cu complexes in the water oxidation reaction. Also, factors such as structure flexibility, electronic properties and the steric effect have a determining influence in terms of the reaction mechanism.…”
Section: Introductionmentioning
confidence: 94%
“…To investigate the relationship between the structure and catalytic activity and to achieve satisfactory performance of Cu complexes, numerous studies have been devoted to designing ligands with different backbone structures as well as ligands with electron-donating or electron-withdrawing functional groups. 21–26 It has been confirmed that the backbone structure of a ligand has an obvious effect on the catalytic activity of Cu complexes in the water oxidation reaction. Also, factors such as structure flexibility, electronic properties and the steric effect have a determining influence in terms of the reaction mechanism.…”
Section: Introductionmentioning
confidence: 94%
“…It has been found that the distal groups on the ligands affect the catalytic activity. [17][18][19][20] On one hand, the electron-donating and electron-withdrawing capabilities of the pendant groups influence the electronic structure of the ligand and the stability of the catalytic active centre. On the other hand, some pendant groups can act as proton relays in the catalytic process.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Meanwhile, the relationship of steady-state catalytic current density ( j cat ) and [ Cat ] fits the formula of j cat = n ′ F [ Cat ]( D cat k cat ) 1/2 ( n ′ = 4 is the total number of electrons transferred for water oxidation to oxygen molecule). 31,32 The estimated turnover frequency (TOF, k cat ) for electrochemical water oxidation can be calculated by a simplified equation: j cat / j d = 1.827( k cat / υ ) 1/2 . The estimated k cat values for 1 and 2 are 0.014 s −1 and 0.027 s −1 , respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%